2011
DOI: 10.1002/humu.21557
|View full text |Cite
|
Sign up to set email alerts
|

On the sequence-directed nature of human gene mutation: The role of genomic architecture and the local DNA sequence environment in mediating gene mutations underlying human inherited disease

Abstract: Different types of human gene mutation may vary in size, from structural variants (SVs) to single base-pair substitutions, but what they all have in common is that their nature, size and location are often determined either by specific characteristics of the local DNA sequence environment or by higher-order features of the genomic architecture. The human genome is now recognized to contain ‘pervasive architectural flaws’ in that certain DNA sequences are inherently mutation-prone by virtue of their base compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
87
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 372 publications
13
87
1
Order By: Relevance
“…1,2 The 1q21.1 duplication was the 11th most common of 28 genomic disorders reported in a recent laboratory survey of clinical microarray results. 3 Consistent with the general tendency for duplications to be less deleterious than deletions and a corresponding ascertainment bias in clinical samples, 4 the 1q21.1 duplication may be rarer than the reciprocal deletion in many, but not all, clinical settings.…”
Section: Introductionmentioning
confidence: 78%
“…1,2 The 1q21.1 duplication was the 11th most common of 28 genomic disorders reported in a recent laboratory survey of clinical microarray results. 3 Consistent with the general tendency for duplications to be less deleterious than deletions and a corresponding ascertainment bias in clinical samples, 4 the 1q21.1 duplication may be rarer than the reciprocal deletion in many, but not all, clinical settings.…”
Section: Introductionmentioning
confidence: 78%
“…Although variants are still often considered as a result of a random process, it is shown that certain regions are inherently variant prone by virtue of their local DNA sequence environment or by higher order features of the genomic architecture. 29 The causal variant described here probably arose because it is part of a CpG dinucleotide variant hotspot. 5 Unravelling these mechanisms might open the way to predict the creation of disease-causing de novo variants.…”
Section: Discussionmentioning
confidence: 94%
“…Repetitive DNA sequences (Cooper et al 2011), including fragile sites (Minca and Kowalski 2011;Thys et al 2015) and Alu (Gu et al 2015) have well-documented associations with genome instability via replication fork-stalling (Ozeri-Galai et al 2011) and stimulation of homology-based recombination processes (Mizuno et al 2013). Although we cannot determine the initiating DNA breakpoint for the telomere fusion events we have sequenced, we did not find any significant coincidence of inter-chromosomal (Cunningham et al 2015) and RefSeq (Pruitt et al 2014) curations-than expected by chance based on RefSeq human genome gene content estimate of 41.8%.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeresmentioning
confidence: 99%